Trust computation in VANET using TOEFV. (2017) - Sharma, Kapil; Chaurasia, Brijesh Kumar; Verma, Shekhar; Bhargava, Arpita
VANET aims to improve road safety by reducing and preventing traffic accidents. The network offers a broad diversity of applications and helps in safety related and infotainment related situations. The distinctive features of VANET, including high density with mobility and open shared wireless medium, may lead VANET suffering from many security vulnerabilities. In this paper, we propose a theory of evidence with the fuzzy analyser in VANET (TOEFV) trust management scheme to increase the security of vehicles. In this work, Dempster Shafer theory is used to evaluate the probability of an event and fuzzy analyser is utilised to evaluate the level of trust. Simulation results show that efficacy of the suggested system.